Evaluation of Job-Mix Formula Tolerances as Related to Asphalt Mixtures Properties (Journal of Engineering, 2018)
The current Iraqi standard specifications for roads and bridges allowed the prepared Job-Mix Formula for asphalt mixtures to witness some tolerances with regard to the following: coarse aggregate gradation by ± 6.0 %, fine aggregate gradation by ± 4.0 %, filler gradation by ± 2.0 %, asphalt cement content by ± 0.3 % and mixing temperature by ± 15 oC. The objective of this work is to evaluate the behavior of asphalt mixtures prepared by different aggregates gradations (12.5 mm nominal maximum size) that fabricated by several asphalt contents (40-50 grade) and various mixing temperature. All the tolerances specified in the specifications are taken into account, furthermore, the zones beyond these tolerances are also observed. The evaluation process is illustrated by volumetric properties such as density, air voids, voids in mineral aggregate and voids filled with asphalt. Marshall test is carried out to find stability and flow values. The resistance to moisture effect is investigated by conducting the compressive test for dry and water immersed conditions to find the index of retained strength. The experimental results supported the recommendations to increase tolerances of coarse and fine aggregate gradations to ± 7.0 % and         ± 5.0 % respectively. The optimum asphalt content tolerance can be increased to ± 0.5 %. The tolerances of filler gradation and mixing temperature are preferable to keep their current values.